Kesulitan mahasiswa calon guru matematika dalam menyelesaikan soal pembuktian matematis pada mata kuliah geometri - Reflina Reflina (Department of Mathematics Education, UIN Sunan Gunung Djati Bandung, West Java, Indonesia, 2020)
The research is aimed to know the difficulties of learning that are faced by students in completing the questions proving math in the eyes of college geometry and knowing the factors that affect the students difficult to resolve the problems of proving mathematics. Research is a research qualitative by using strategies case study research that aims to describe the difficulties of students in solving mathematical proof problems with descriptive analysis methods. Difficulties are referred to is the difficulty in the concept and principles of geometry. The subjects of this study were 3th semester of Mathematics Education students at Islamic State University of North Sumatera Medan, academic year 2019/2020 PMM1 class consisting of 39 students. The instrument was the test which consisted of 4 proof problems at geometry, interview and documentation. Difficulties students in learning geometry includes things following namely : the student is difficult to respond to what the intention and purpose matter, is difficult determine the beginning or the beginning of a proof, difficult to find an idea and notion, difficult to apply the definition, nature, and the theorem in constructing the proof , and students still difficult to think logically determine the steps proving that true . The type of error that predominantly occurs in the model answers of students, in the form of the type of error the data is not appropriate, procedures are not appropriate, the conflict level of response, and the problem hierarchy of skills. Factors that make the students difficult to learn geometry, namely the factor of matter which is considered difficult to understand, apply, and applied in solving the problem